(untitled) (PerCursos, 2023)
Our interest focuses on the study of centenarian residents in Argentina. Between the 2001 and 2010 censuses, the number of Argentinean centenarians doubled, going from 1855 to 3500 people, respectively. Based on the life course paradigm, our objective is to analyze the life trajectories of centenarians to assess their family arrangements, their health perception, and the strategies they devised to deal with everyday life. We focused on the reconstruction of life trajectories, identifying the domains in which centenarians perceived changes, and on their subjective appraisals of said changes in terms of gains and losses. A qualitative case study methodology was designed, using in-depth interviews. Sample preparation is currently underway, and it presently consists of eight cases. The main results show that the interplay between gains and losses over the life course responds to the standard life course model, in which gains are more frequent during youth, and losses are predominant afterwards. Nonetheless, there are gains typical of the great old age, linked to family life, free time, and religion. Also, centenarians play a support role across their primary networks.